Effect of Platycodon grandiflorus Polysaccharide on M1 Polarization Induced by Autophagy Degradation of SOCS1/2 Proteins in 3D4/21 Cells - Li, Liping; Chen, Xufang; Lv, Meiyun; Cheng, Ziqiang; Liu, Fang; Wang, Ying; Zhou, Aiqin; Liu, Jianzhu; Zhao, Xiaona (Frontiers in Immunology, 2022)
M1 polarized macrophages can improve the body ' s immune function. This study aimed to explore the mechanism of Platycodon grandiflorus polysaccharide (PGPSt) degrading SOCS1/2 protein through autophagy and promoting M1 polarization in 3D4/21 cells. Immunoprecipitation, confocal laser scanning microscopy, flow cytometry and intracellular co-localization were used to detect the expression of related phenotypic proteins and cytokines in M1 polarized cells. The results showed that PGPSt significantly promoted the mRNA expression of IL-6, IL-12 and TNF-α, and enhanced the protein expression of IL-6, IL-12, TNF-α, IL-1β, iNOS, CD80 and CD86, indicating that PGPSt promoted M1 polarization in 3D4/21 cells. Next, the effect of PGPSt autophagy degradation of SOCS1/2 on M1 polarization of 3D4/21 cells was detected. The results showed that PGPSt significantly down-regulated the expression level of SOCS1/2 protein, but had no obvious effect on the mRNA expression level of SOCS1/2, indicating that PGPSt degraded SOCS1/2 protein by activating lysosome system. Further research found that under the action of 3-MA and BafA1, PGPSt up-regulated LC3B II and down-regulated SOCS1/2 protein expression, which increased the possibility of LC3B, the key component of autophagy, bridging this connection and degrading SOCS1/2. The interaction between SOCS1/2 and LC3 was identified by indirect immunofluorescence and Co-IP. The results showed that the co-localization percentage of the two proteins increased significantly after PGPSt treatment, and LC3 interacted with SOCS1 and SOCS2. This provides a theoretical basis for the application of PGPSt in the treatment or improvement of diseases related to macrophage polarization by regulating autophagy level.